The bees (Hymenoptera: Apoidea) of the Maltese Islands - Balzan, Mario V.; Rasmont, Pierre; Kuhlmann, Michael; Dathe, Holger; Pauly, Alain; Patiny, Sébastien; Terzo, Michael; Michez, Denis (Zootaxa, 2016)
This study presents the first checklist of the bees of the Maltese Islands and includes notes on the distribution of each species. A total of 95 species belonging to five bee families are recorded: Andrenidae (17 species), Apidae (34 species), Colletidae (6 species), Halictidae (15 species) and Megachilidae (23 species). Lasioglossum callizonium (Pérez, 1896) is recorded for the first time from the Maltese Islands. Records of three previously reported species are listed as dubious. The bee fauna of the Maltese Archipelago is dominated by widespread West-Palaearctic species, and most of the species recorded are also found in the Western Mediterranean Basin. Bees that have been recorded from Malta are also known from Southern Europe. The study provides a biogeographical analysis of the Maltese bee fauna, and discusses the conservation of this group and their important role in the delivery of ecosystem services in the Maltese Islands.